Comparison of Bier’s block with Lidocaine versus Lidocaine plus Verapamil - Tabdar, S; Lama, S; Kadariya, ER (Journal of Kathmandu Medical College, 2014)
Background: General anaesthesia and regional anaesthesia both are used for upper extremity surgeries. Bier’s Blockusing local anaesthetic alone or in combination with other adjuvants provides effective analgesia intraoperatively as wellas postoperatively with fewer complications as compared to general anaesthesia. Objective: This study was designed to compare effectiveness, haemodynamic alterations and total duration of analgesiawith Lidocaine versus Lidocaine plus Verapamil in Bier’s Block. Methods: This is a prospective randomised double blind trial conducted in Kathmandu Medical College TeachingHospital from February 2012 to December 2012 after approval from the ethical committee and informed consent fromthe participants. Total 40 adult patients of age 20 to 50 years, weight 50 to 70 kg, of both gender, belonging to AmericanSociety of Anaesthesiologists Physical Status I and II undergoing elective distal upper extrimity surgery lasting at one toone and half hours with Bier’s Block were included in this study. They were randomly divided into two groups of twentyeach to receive either 40 ml of 0.5% Lidocaine alone (Group A) or 40 ml of 0.5% Lidocaine plus 2.5 mg Verapamil (GroupB). The two groups were compared in terms of onset and recovery from sensory and motor blockade, tourniquet paintolerance time, duration of analgesia, alteration of haemodynamics and major side effects. Data analysis was done byMicrosoft Offi ce Excel 2007 [Polystat, Microsoft Offi ce Excel worksheet.XLS] using student’s two tailed t test. Categoricalparamatres were tested by Fisher Exact test and p-value of <0.05 was considered statistically signifi cant. Result: Onset of sensory blockade was faster in group B (Mean± SD: 3.07± 0.25 minutes) as compared to group A (Mean±SD: 5.59 ± 0.41 minutes). The onset of motor block in group B was 10.4 ± 0.77 minutes versus 13.17 ± 1.45 minutes ingroup A. Recovery of sensory block in group B occurred at 29.95 ± 6.96 minutes versus 11.45 ± 2.16 minutes in groupA. Similarly recovery of motor block in group B occurred in 13.6 ± 1.79 minutes versus 7.65 ± 1.04 minutes in group A.Tolerance of fi rst tourniquet pain in group B was long 41.15 ± 3.82 minutes versus 22.00 ± 2.9) minutes in group A. Secondtourniquet pain tolerance time was again longer (48.25 ± 3.96 minutes) in group B versus 28.05 ± 4.84 minutes in groupA. Total duration of analgesia was more in group B (207.25 ± 21.1 minutes) versus 32.2 ± 5.78 minutes in group A. Totalconsumption of analgesic (Tramadol) in 24 hours in group B was lesser than group A (47.5 ± 38.0 mg versus 112.5 ± 35.8mg). All these differences were signifi cant statistically (p value <0.05). Both of the groups showed stable haemodynamicparameters intraoperatively as well as postoperatively without any signifi cant adverse effects. Conclusion: Addition of Verapamil to Lidocaine was more effective than Lidocaine alone in Bier’s block. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10513 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, Page: 12-17